Joint impact of Philanthropy and Corporate Reputation on Firm Value - Daromes, Fransiskus Eduardus; Gunawan, Stevi Revigi (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
This study investigates the effect of philanthropy on firm value with company reputation as a moderating variable. The population used in this study are all non-financial companies listed on the Indonesian Stock Exchange during (IDX) 2015 - 2017. Total samples are 38 companies for the 3 years selected by purposive sampling. This study uses secondary data, i.e. annual report, financial report, and sustainability report collected from IDX database and each companyÃ¢â‚¬â„¢s official website. The results of the analysis show that the effect of philanthropy on firm valuehas a non-significant effect. The findings also indicate that corporate reputation is able to moderate the influence of philanthropy on firm value. This finding implies that the role of corporate reputation is very important for the survival of the company.Ã‚Â The good relationship between the company and their stakeholders, especially the community through philanthropic activities will increase the firm value and corporate reputation.